Mediation in the Activities of a Lawyer - Kraemer, Raimonda (Teisė, 2023)
The article presents the results of the research and reveals the following: do lawyers use mediation in their activities, how often do they do it; how do lawyers evaluate their activities in mediation, what are the reasons for this. Is the lawyers’ knowledge of mediation sufficient, what influence does the mediator’s qualification have on this; how lawyers value mediation, what is their attitude towards this method of ADR; whether and how well lawyers are able to provide clients with information about mediation and what is the opinion of lawyers regarding the most suitable profession for the role of mediator.
Keywords: mediation; lawyer; client; parties to the dispute; recommend; do not recommend; amicable settlement of the dispute